2015
DOI: 10.1080/15389588.2014.973945
|View full text |Cite
|
Sign up to set email alerts
|

Driving Fatigue in Professional Drivers: A Survey of Truck and Taxi Drivers

Abstract: This study provides knowledge on truck and taxi drivers' characteristics in fatigue experience, fatigue attitude, and fatigue countermeasures, and these findings have practical implications for the fatigue management and education of professional drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 53 publications
2
77
0
Order By: Relevance
“…Various analysis techniques have been used by the researchers to study the effects of different lifestyle and sleep-related factors on the probability of drowsy driving and associated crash risk. For instance, Girotto et al (2016) and Sadeghniiat-haghighi et al (2016) used multinomial logistic regression and Häkkänen and Summala (2001), Meng et al (2015), Papadakaki et al (2008) and Tzamalouka et al (2005) used logistic regression. Chi-square test (Meng et al, 2015;Williamson & Friswell, 2013), Kruskal-Wallis test (Philip et al, 2002;Sabahiah et al, 2017), Spearmen correlation (Philip et al, 2002), factor analysis (McCartt et al, 2000;Sullman et al, 2002;Tsao, Chang, & Ma, 2017), multivariate analysis of covariance (MANCOVA) (Thompson & Stevenson, 2014) and Agent-Based Modeling (ABM) (Thompson et al, 2015) are also some of the commonly used analysis techniques.…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Various analysis techniques have been used by the researchers to study the effects of different lifestyle and sleep-related factors on the probability of drowsy driving and associated crash risk. For instance, Girotto et al (2016) and Sadeghniiat-haghighi et al (2016) used multinomial logistic regression and Häkkänen and Summala (2001), Meng et al (2015), Papadakaki et al (2008) and Tzamalouka et al (2005) used logistic regression. Chi-square test (Meng et al, 2015;Williamson & Friswell, 2013), Kruskal-Wallis test (Philip et al, 2002;Sabahiah et al, 2017), Spearmen correlation (Philip et al, 2002), factor analysis (McCartt et al, 2000;Sullman et al, 2002;Tsao, Chang, & Ma, 2017), multivariate analysis of covariance (MANCOVA) (Thompson & Stevenson, 2014) and Agent-Based Modeling (ABM) (Thompson et al, 2015) are also some of the commonly used analysis techniques.…”
Section: Previous Researchmentioning
confidence: 99%
“…In contrast to India, the previous studies across the globe have elucidated the dimensions of drowsiness problem among commercial or Heavy Vehicle (HV) drivers to some extent (Duke et al, 2010;Castillo-Manzano et al, 2016;Teoh et al, 2017;Meng et al, 2015;Kanazawa et al, 2006). Based on the literature, the major contributing factors to drowsiness problem among drivers are discussed in the following sub-sections.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, drivers' vocation was another factor related to traffic violations and road crashes [48]. Professional drivers (such as taxi, bus, or truck drivers) had a high probability of traffic crashes due to a high exposure on road and the high possibility of fatigue driving [49]. Moreover, professional drivers may perform differently from nonprofessional drivers because of different levels of driving skills.…”
Section: Impacts Of Driver Characteristics On Driver Behaviormentioning
confidence: 99%
“…Many factors contributed to driving fatigue for taxi drivers, among which prolonged driving time was likely to be the most common and important [30]. Meng et al [31] found that the reason for the engagement in prolonged driving was neither a lack of awareness concerning the serious outcomes of fatigue driving nor poor detection of fatigue. e most probable reason was optimism bias, which led these professional drivers to think that fatigue was more serious for other drivers than for themselves and that they were effective in counteracting the effect of fatigue on their driving performance.…”
Section: Introductionmentioning
confidence: 99%